Characterizing lentic habitats in golf courses and adjacent green spaces: water quality, water chemistry, pesticide concentrations, and algal concentrations. Issue 1 (23rd November 2020) - Piacente, Jennifer N.; Milanovich, Joseph R.; Berg, Martin B.; Hoellein, Timothy J.; Muñoz, Andrés G.; Cann, Armand A.; Lentini, Isabella S.
Abstract: As human-dominated land-use increases globally, urbanization is a prominent cause of a decline in natural areas, including lentic ecosystems (i.e. lakes, ponds and wetlands). Lentic ecosystems in urban green spaces, such as parks, golf courses or forest preserves, could provide important habitat for organisms within the urban matrix. However, there is a lack of data comparing lentic habitats across these land-use types. We quantified the area of golf courses and forest preserve habitats in the Chicago Metropolitan Region. We measured pesticide concentrations, water chemistry, physicochemical parameters and algal composition in lentic habitats of golf courses and forest preserves in the spring and summer of 2017. Permanent ponds, whether located within a golf course or forest preserve, had similar water quality, chemistry and chlorophyll a and phycocyanin, but differed from ephemeral ponds in forest preserves. Pesticide concentrations within golf course ponds were found in 11 of 25 courses, but only three pesticides (out of 10 measured) were detected. These data suggest golf courses can provide lentic habitats of similar quality to other adjacent land-use types. Additional study is needed to document their role in providing habitat for aquatic biota and sustaining ecosystem services in urban landscapes.